2015
DOI: 10.1038/ejcn.2015.6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of brief dietary questionnaires suitable for clinical use in the prevention and management of obesity, cardiovascular disease and type 2 diabetes

Abstract: The aim of this systematic review was to identify and describe brief dietary assessment tools suitable for use in clinical practice in the management of obesity, cardiovascular disease and type 2 diabetes. Papers describing development of brief (<35 items) dietary assessment questionnaires, that were accessible, simple to score and assessed aspects of the diet of relevance to the conditions of interest were identified from electronic databases. The development of 35 tools was described in 47 papers. Ten tools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 66 publications
(164 reference statements)
3
59
0
1
Order By: Relevance
“…The degree of association between the number of portions of fruit and vegetables consumed measured by the PVS-SQ and PREDIMED FFQ presented statistically significant differences according to sex, with a moderate to high association for women and low association for men. Reliability is similar to that found in other studies made outside the context of PHC, ranging between 0.52 and 0.95 [37, 38]. Other studies confirmed the pattern of men consuming fewer servings of fruit and vegetables daily than women [37, 3941], and found similar differences (2.52 vs. 3.47; P  < 0.01) in Baker et al [40].…”
Section: Discussionsupporting
confidence: 88%
“…The degree of association between the number of portions of fruit and vegetables consumed measured by the PVS-SQ and PREDIMED FFQ presented statistically significant differences according to sex, with a moderate to high association for women and low association for men. Reliability is similar to that found in other studies made outside the context of PHC, ranging between 0.52 and 0.95 [37, 38]. Other studies confirmed the pattern of men consuming fewer servings of fruit and vegetables daily than women [37, 3941], and found similar differences (2.52 vs. 3.47; P  < 0.01) in Baker et al [40].…”
Section: Discussionsupporting
confidence: 88%
“…The UKDDQ results are comparable to the results obtained for the NSQ and MEDAS. Formal evaluation of the time to complete the UKDDQ was not conducted; however, informal feedback from patients and nurses indicates that most people took about 5–10 min, which is consistent with similar-length questionnaires ( 12 ) .…”
Section: Discussionmentioning
confidence: 56%
“…We recently conducted a review of brief dietary questionnaires that can be used to rapidly assess diets in a clinical setting ( 12 ) . These tools demonstrated good-to-excellent relative test–retest reliability (correlation coefficients ranged from 0·59 to 0·95) and moderate-to-good relative agreement with diet records (correlations ranged from 0·16 to 0·79; the majority of tools demonstrated correlations of between 0·30 and 0·50).…”
mentioning
confidence: 99%
“…83 A review of the 35 brief questionnaires designed to score intake on the basis of recommended foods (eg, fruits and vegetables) or dietary patterns (eg, DGA or the Mediterranean diet) concluded that similarity of the clinical population to the study population and the measurement characteristics of the instrument are important considerations. 84 Patient and public education has historically used food group dietary planning methods. 85 Simplified assessment tools can promote self-monitoring based on dietary pattern recommendations.…”
Section: Examples Of Ongoing Tools For Dietary Self-monitoringmentioning
confidence: 99%